(3SjQI GdMGLH LYaQ Hf Ydi hNQhL GdegOi ef SdejI hhUhd Edi SdLeGSI (B( (3aj GdOYhI GdaGWejI (B)s - (3eMeO Hf eMeO GdjeGfjs
(3ChdgG (B:s
(3CSCd Gddg GdJhajb deG jQVjg hjQVi hdjg hehdGfG CejQ GdeDefjf s
(3BNQgG (B:s
(3Je GdNjQ , hGdMeO ddg ChdkG hBNjQkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B16 - (3U(B57s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B236 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(11497(3M(B) s
Keywords: (3GdJGQjNs